2019
DOI: 10.1021/acs.jpcb.8b12088
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics Simulation and Energetics of the Ribulose-1,5-biphosphate Carboxylation Reaction Catalyzed by Rubisco: Toward Elucidating the Stereospecific Protonation Mechanism

Abstract: In the carboxylation reaction catalyzed by ribulose 1,5-bisphosphate (RuBP) carboxylase–oxygenase (Rubisco), which is fundamental to photosynthesis, scission of a C–C bond in the six-carbon gemdiolate intermediate forms a carbanion that must be protonated stereospecifically to form product. It is thought that a conserved lysine side chain (LYS175 in spinach Rubisco), in the immediate vicinity of the carbanion, provides the necessary proton. Here, we endeavor to determine from the electronic-structure calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…1,2,[4][5][6][7][8][9] Within the enzyme's catalytic pocket, a set of five chemical reactions convert the initial substrate, ribulose 1,5-bisphosphate (RuBP), to the final product, two-molecules of 3-phosphoglycerate (3-PGA). [4][5][6]10,11 The catalyzed chemical reactions involve CO 2 and H 2 O addition to an activated RuBP intermediate by enolization, which subsequently undergoes a bond dissociation reaction to produce two-molecules of 3-PGA through stereospecific protonation. 5,6,[10][11][12] All these chemical transformations (enolization, carboxylation, hydration, bond cleavage and stereospecific protonation) occur in a highly charged chemical environment centered on the first magnesium (II) coordination sphere (see Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,[4][5][6][7][8][9] Within the enzyme's catalytic pocket, a set of five chemical reactions convert the initial substrate, ribulose 1,5-bisphosphate (RuBP), to the final product, two-molecules of 3-phosphoglycerate (3-PGA). [4][5][6]10,11 The catalyzed chemical reactions involve CO 2 and H 2 O addition to an activated RuBP intermediate by enolization, which subsequently undergoes a bond dissociation reaction to produce two-molecules of 3-PGA through stereospecific protonation. 5,6,[10][11][12] All these chemical transformations (enolization, carboxylation, hydration, bond cleavage and stereospecific protonation) occur in a highly charged chemical environment centered on the first magnesium (II) coordination sphere (see Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6]10,11 The catalyzed chemical reactions involve CO 2 and H 2 O addition to an activated RuBP intermediate by enolization, which subsequently undergoes a bond dissociation reaction to produce two-molecules of 3-PGA through stereospecific protonation. 5,6,[10][11][12] All these chemical transformations (enolization, carboxylation, hydration, bond cleavage and stereospecific protonation) occur in a highly charged chemical environment centered on the first magnesium (II) coordination sphere (see Figure 1A). 4,5 In the last five decades, much effort has been devoted to studying the mechanisms of RuBisCO carboxylase activity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2,4–9 ] Within the enzyme's catalytic pocket, a set of five chemical reactions convert the initial substrate, ribulose 1,5‐bisphosphate (RuBP), to the final product, two‐molecules of 3‐phosphoglycerate (3‐PGA). [ 4–6,10,11 ] The catalyzed chemical reactions involve CO 2 and H 2 O addition to an activated RuBP intermediate by enolization, which subsequently undergoes a bond dissociation reaction to produce two‐molecules of 3‐PGA through stereospecific protonation. [ 5,6,10–12 ] All these chemical transformations (enolization, carboxylation, hydration, bond cleavage, and stereospecific protonation) occur in a highly charged chemical environment centered on the first magnesium (II) coordination sphere (see Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…[ 5,6,10–14 ] Computational and experimental studies have identified the role of different amino‐acid residues within each chemical step. [ 4–7,10–24 ] Specifically, Gready et al [ 5 ] have proposed a complete sequence of chemical species that connect the initial RuBP with the two‐molecules of 3‐PGA from calculations on a set of model fragments representing the active‐site and substrate. These models represent the first magnesium coordination sphere including a reduced version of the substrate and the protonated residues Kcx201 (carbamylated lysine), Asp203 and Glu204 together with the second magnesium coordination sphere consisting of residues His294, Lys334, Lys177, and Lys175, schematically shown in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation